2007
DOI: 10.1016/j.expneurol.2007.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Detection of traumatic axonal injury with diffusion tensor imaging in a mouse model of traumatic brain injury

Abstract: Traumatic axonal injury (TAI) is thought to be a major contributor to cognitive dysfunction following traumatic brain injury (TBI), however TAI is difficult to diagnose or characterize non-invasively. Diffusion tensor imaging (DTI) has shown promise in detecting TAI, but direct comparison to histologically-confirmed axonal injury has not been performed. In the current study, mice were imaged with DTI, subjected to a moderate cortical controlled impact injury, and re-imaged 4-6 hours and 24 hours post-injury. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
209
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(235 citation statements)
references
References 85 publications
20
209
1
1
Order By: Relevance
“…For example, DTI and other advanced neuroimaging techniques can elucidate signal changes in the white matter that have been shown to correlate with axonal pathology in animal models. [106][107][108][109][110] In humans with mild TBI, DTI has also shown changes in the white matter, including both increases and decreases in fractional anisotropy and other DTI-related metrics that evolve over time. [111][112][113][114][115][116][117] In some cases, these imaging changes have been linked to varying degrees of morbidity, suggesting a causal relationship.…”
Section: Advanced Neuroimagingmentioning
confidence: 99%
“…For example, DTI and other advanced neuroimaging techniques can elucidate signal changes in the white matter that have been shown to correlate with axonal pathology in animal models. [106][107][108][109][110] In humans with mild TBI, DTI has also shown changes in the white matter, including both increases and decreases in fractional anisotropy and other DTI-related metrics that evolve over time. [111][112][113][114][115][116][117] In some cases, these imaging changes have been linked to varying degrees of morbidity, suggesting a causal relationship.…”
Section: Advanced Neuroimagingmentioning
confidence: 99%
“…Recent experimental data indicate that white matter abnormalities detected using DTI correlate closely with neuropathological evidence of diffuse axonal injury. 28,29 In a prospective study, Sidaros et al evaluated 30 patients with severe TBI at 8 weeks and 12 months after injury. They found that decreased regional FA at 8 weeks was predictive of unfavorable outcome at 12 months.…”
Section: Critical Care Medicinementioning
confidence: 99%
“…The optical fractionator technique was used to count a systematic random sample of positively-stained axonal varicosities over the entire rostral to caudal extent of the region of interest. Details of these stereological methods have been previously described (Mac Donald et al, 2007a,2007bShitaka et al, 2011;Tran et al, 2011). In brief, for quantification of APP-stained axonal varicosities and Iba1-stained microglia, the region of the corpus callosum and external capsule from each coronal slice was outlined at low power (4 · ), followed by systematic counts of objects of interest at high power (60 · , oil immersion), of sites within the counting region randomly chosen by the StereoInvestigator software.…”
Section: Stereological Quantificationmentioning
confidence: 99%